A study on perception towards impacts of PATI among employees in Majls Perbandaran Sandakan (MPS) / Nurhaina Kirang and Sitti Noor Syahhedah Yusuf - Kirang, Nurhaina; Yusuf, Sitti Noor Syahhedah (2015)
According to Agnes and Geralnik (1999), Illegal immigrant is the person who come into new country, region, or environment, especially in order to settle there or called unauthorized alien. They come into two ways, entering a country without the required valid documentation and remaining in a country without valid documentation. Illegal immigrants simply wish to offer various industries their cheap labor in order to gain easy access to public goods and services. Illegal immigrant that come into country is experiencing or indulging government or public facilities together with local people, specifically towards locals that are entitled to pay compulsory taxes such as road tax, housing tax, income tax and etcetera. While in terms of others perspectives, illegal immigrant can exploit governmental political system, snatch employment opportunity from locals, riding out problems of security and society peace and such. Illegal immigrant had been an issue ever since post-independent years in Malaysia. Since the implementation of Immigration Act 1959, the entry of immigrations, lead to being foreigner workers enabling the penetrations of several of immigrations, that once government had no problem to control, but not until it turned into massive entry of illegal immigrants. The permission of illegal immigrants into Malaysia began through 1970's to 1980's. The nation those years were in dependant and reliance towards foreign workers to support Malaysia's growth strategy.